Social vulnerability by gender: potential risks to climate change in Mexico - Granados Martinez, Abraham (2017)
Population risks from climate change are the result of a factors combination of physical, social, economic and regional. The goal in this article is identify and show social vulnerability differentiated for women and men about potential risks of climate change in Mexico. Social vulnerability is determined in six dimensions: income, health, education, housing, population factors and dependence on agriculture. This research finds that women are more vulnerable in terms of income, while men are highly active in agriculture, which impairs adaptation and resilience to the risks associated with climate change. It is appropriate to take actions differentiated by sex and at the regional level to address social vulnerability to the risk of climate change, such as policies to improve women's income and favor their opportunities for economic empowerment and provide additional employment opportunities for men Employed in agriculture, especially for areas with high potential to be affected by climate change.